T-cell leukemogenesis is an inappropriate lineage decision-making process: implications for precision oncology. (4th July 2018) - Rodríguez-Hernández, Guillermo; Bhatia, Sanil; Vicente-Dueñas, Carolina; Borkhardt, Arndt; Hauer, Julia; Sánchez-García, Isidro
ABSTRACT: Genetic lineage tracing in cell type-specific mouse models of T-cell acute lymphoblastic leukemia (T-ALL) have revealed that tumor cell identity is imposed by expression of the oncogene Lim Domain Only 2 ( LMO2), rather than by the target cell phenotype. This approach allowed to identify that secondary genomic alterations, like Notch1 mutations, appeared late and only took place within the thymus during T-ALL development. These concepts are therefore critical for the development of modern therapies aimed at curing T-ALL.